Empirical investigation on GOE-EGDMS usage frequency in the Malaysian e-government agencies / Mohd Redzuan Mohd Jamaraji - Mohd Jamaraji, Mohd Redzuan (2006)
The primary objective of most document management system is to reduce time of document preparations, retrieving and to enhance communication between co-workers. This independent study presents the internal government employees aspect of document management system. Generic Office Environment - Electronic Government Document Management System (GOE-EGDMS) is one of seven flagship of electronic government information system. The aim is to understand how government employees perceive GOE-EGMDS as a primary document management channel and the factors that affect their level of usage. This independent study measured the usages of GOE-EGDMS among government staffs. At implemented agencies, system usage frequency collected through database server for six month continuously. Online questionnaire distributed via one of the GOE-EGDMS module, namely Forum. The empirical evidence has been grouped under two key factors, gender and job responsibilities (service group). Analyzing system usage frequency and correlation between gender and service group indicated system usage is vaguely influenced by gender, but is auxiliary by job responsibilities. The benefit of this study is not specific to particular case but it is potentially generalizable whereby it can provide some clues for e-government officials to implement e-government project more effectively and help e-government researchers to identify some important framework constructs regarding the adoption of e-government.